Hubungan Kausalitas Workplace Spirituality Dan Kinerja Karyawan: Perspektif Mediasi Etika Kerja Islam - Umam, Moh Rifqi Khairul; Auliya, Zakky Fahma (BISNIS, 2017)
Human resource is a very important element in achieving organizational goals. If the organization has a good quality of resources, the organization will be more effective. While the effectiveness of the organization is reflected from the employee performance. The purpose of this study is to examine the effect of workplace spirituality on Islamic work ethic, Islamic work ethic on employee performance, workplace spirituality on employee performance, and the influence of Islamic work ethic as an intervening variable on the relation between workplace spirituality and employee performance, with samples from PKU Muhammadiyah Surakarta Hospital, and IPHI Pedan Hospital, Klaten. The result of the research shows that workplace spirituality has significant effect on Islamic work ethic with, Islamic work ethic has no significant effect to employee performance, workplace spirituality has no significant effect to employee performance, and Islamic work ethic as mediation variable on relation between workplace spirituality (STK) to employee performance has no significant influence.